The Impact of ICT and Robots on Labour Market Outcomes of Demographic Groups in Europe - Maciej Albinowski; Piotr Lewandowski (Institute of Labor Economics (IZA), 2022)
We study the age- and gender-specific labour market effects of two key modern technologies, Information and Communication Technologies (ICT) and robots, in 14 European countries between 2010 and 2018. To identify the causal effects of technology adoption, we utilise the variation in technology adoption between industries and apply the instrumental variables strategy proposed by Acemoglu and Restrepo (2020). We find that the exposure to ICT and robots increased the shares of young and prime-aged women in employment and the wage bills of particular sectors, but reduced the shares of older women and prime-aged men. The adverse effects were particularly pronounced for older women in cognitive occupations, who had relatively low ICT-related skills; and for young men in routine manual occupations, who experienced substitutions by robots. Between 2010 and 2018, the growth in ICT capital played a much larger role than robot adoption in the changes in the labour market outcomes of demographic groups.
Keywords: J24; O33; J23; 330; technological change; automation; ICT; robots; employment; wages; Europe